Distribution of levels of soil contamination by heavy metals in the Ivanovo and Kostroma regions, Russia - A. N. Sivukhin; D. S. Markov; I. B. Noda (Юг России: экология, развитие)
Aim. Identify potential sources of heavy metal contamination of soil in the Ivanovo and Kostroma regions, Russia. Identify the risks to public health in the regions studied.Material and Methods. 72 sampling sites were laid out. Laboratory preparation of extracts from soil samples was carried out in the facilities of the Biological‐Chemical Faculty of Ivanovo State University. Hardware analysis was undertaken using a 210 VGP atomic absorption spectrophotometer. Statistical and mathematical data processing was carried out with the OpenOffice Calc open‐source software package. The plotting of cartographic materials was done with Quantum GIS Brighton. Since soils are often contaminated with several elements at the same time, the total pollution index (Zc) was calculated for them, thus reflecting the effect of exposure of the groups of elements.Results. Significant excesses above the maximum permissible concentrations (MPC) for cobalt, lead, and cadmium were not found in spring soil samples. The average pollution value Zc for the Ivanovo region was 20 units (a significant pollution level) and for Kostroma ‐ 38 (a high pollution level). The hazard coefficient for the content of heavy metals in the soil cover of the Ivanovo region is thus in the second range (significant risk), while in the soil cover of the Kostroma region it is in the third range (high risk).Conclusions. Mostly heavy metals enter the soil from solid waste dumps and also settle during the snowless season. There is a risk to public health.